Building patient trust in health systems: A qualitative study of facework in the context of the Aboriginal and Torres Strait Islander Health Worker role in Queensland, Australia. (June 2022) - Topp, Stephanie M.; Tully, Josslyn; Cummins, Rachel; Graham, Veronica; Yashadhana, Aryati; Elliott, Lana; Taylor, Sean
Abstract: Healthcare services in Australia are the primary responsibility of state and territory governments, which recruit and deploy health providers in hospital and primary-care services. Among the various health professional roles, that of Aboriginal and Torres Strait Islander Health Worker (A&TSIHW) is one of only two positions that must be occupied by an Aboriginal and/or Torres Strait Islander person, carrying unique responsibility for enacting cultural brokerage and promoting cultural safety at the facility-level. Implicit to these responsibilities is the assumption that A&TSIHW will use cultural capital to build clients' trust in themselves and ultimately the broader health system. Drawing on 82 in-depth interviews including 52 with A&TSIHWs, we applied Kroegar's Facework theory to explore the structures, processes and relationships that contribute to, or inhibit, A&TISHWs' capacity and willingness to build trust (beyond themselves) in government health services in Queensland, Australia. Analysis demonstrates that despite A&TSIHWs viewing and enacting interpersonal trust-building as central to their role, structural features of the health system inhibit the development of service-users' system-level trust. Findings re-establish that health systems are not 'cultureless, ' but rather, shaped by a dominant culture that privileges certain actors, types of knowledge, and modes of communication and action, which in turn influence efforts to build trust. The study demonstrates a novel theory-driven approach to exploring the interactions between behavioural and structural factors that influence the production of systems-level trust. In the context of the Queensland public health service findings highlight a disconnect between the expectations of, and support provided to A&TISHWs to engage Aboriginal and Torres Strait Islander service-users. Highlights: Aboriginal and Torres Strait Islander Health Workers (A&TSIHWs) are boundary spanners. Building interpersonal trust with clients is central to their work. But health system structures including racism weaken their role as builders of system-level trust. We provide a theoretical basis for linking health system structure to provider and service-users' trust. Absent structural reform, hyper-localized interventions will not improve system-level trust among marginalized populations.